Alopecia in children undergoing chemotherapy, radiation, and hematopoietic stem cell transplantation: Scoping review and approach to management. Issue 3 (13th April 2022) - Kessler, Stephen; Marzooq, Ali; Sood, Arun; Beebe, Kristen; Walsh, Alexandra; Montoya, Liliana; Price, Harper
Abstract: Alopecia is a common sequela in children undergoing chemotherapy, radiation, and hematopoietic stem cell transplantation. In most cases, this is a transient state in which full hair regrowth eventually occurs, but permanent or persistent alopecia, defined as the presence of incomplete hair regrowth more than 6 months after cessation of treatment, is possible and can be psychologically distressing. We sought to characterize the risk factors that can lead to permanent alopecia following the aforementioned treatments in pediatric populations, as well as diagnostic and treatment options that may be considered, as part of a scoping review of the literature. A general algorithm for approaching these patients was developed based on our findings.